Introducing the “urine biochemical approach”: an alternative tool for improving acute kidney injury monitoring in critically ill patients - Maciel, Alexandre Toledo (Frontiers in Nephrology, 2025)
Urine electrolytes and indices assessment as a tool for acute kidney injury (AKI) pathophysiological understanding and management is, until these days, a matter of debate. The classic division of AKI in “pre-renal” (functional/transient) and “renal” (structural/persistent) based on the urinary concentration of sodium and the fractional excretions of sodium and urea has gained popularity for decades and is still present in medical textbooks. Nevertheless, the conclusions of the studies that have used these parameters are very heterogenous and controversial. In the last decade, the pre-renal paradigm has been questioned since urine biochemistry (UB) compatible with “pre-renal AKI” was retrieved from experimental animals with increased renal blood flow, leading some authors to conclude that this approach is not useful for AKI monitoring. Our group has also studied the use of UB in AKI and we think that the key point for adequate use of this tool in clinical practice is a complete mindset change in the way we look and interpret data. In this article, we present the “urine biochemical approach” as an alternative way for UB assessment, which we believe that makes more sense and seems to be more useful for AKI monitoring than the traditional approach. Although the real utility of this alternative approach needs to be confirmed in large, prospective studies, the aim of the present article is to open the mind of critical care practitioners for a potential reappraisal of ancient concepts and ideas regarding the use of urine electrolytes in AKI monitoring.